👤
a fost răspuns

52-{2+3x[2+3x(2+2x3):2-2x3]x2}=



Răspuns :

52-{2+3x[2+3x(2+6):2-6]x2}=                                                                                52-[2+3x(2+3x8:2-6)x2]=                                                                                    52-[2+3x(2+12-6)x2]=                                                                                        52-(2+3x8x2)=                                                                                                    52-(2+48)=                                                                                                        52-50=2